2003
DOI: 10.1046/j.1365-313x.2003.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

EXORDIUM– a gene expressed in proliferating cells and with a role in meristem function, identified by promoter trapping in Arabidopsis

Abstract: To identify new genes expressed in meristematic cells, a promoter trap insertional mutagenesis strategy was used in Arabidopsis thaliana. Transgenic line AtEM201 exhibits promoter trap GUS activity in embryos and in the regions of active cell division in the seedling, notably the apical meristems and young leaves. The tagged gene was named EXORDIUM (EXO). AtEM201 contains a single copy of the promoter trap T-DNA, located in the EXO gene promoter, resulting in a much reduced level of EXO transcription. Seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…This extracellular EXO gene was identified as a potential mediator of BR-promoted growth [36], and it is part of a gene family with eight members in arabidopsis. As EXO is presumably involved in a signaling process which coordinates BR-responses with environmental or developmental signals, it cannot be ruled out that EXO protein might be involved in cell enlargement associated with the early induction of melon MFA.…”
Section: Resultsmentioning
confidence: 99%
“…This extracellular EXO gene was identified as a potential mediator of BR-promoted growth [36], and it is part of a gene family with eight members in arabidopsis. As EXO is presumably involved in a signaling process which coordinates BR-responses with environmental or developmental signals, it cannot be ruled out that EXO protein might be involved in cell enlargement associated with the early induction of melon MFA.…”
Section: Resultsmentioning
confidence: 99%
“…2 showed homology to EXORDIUM ( EXO ), which has a role in meristem function in Arabidopsis [65], cell expansion and brassinosteroid (BR)-mediated responses [66] and growth during low carbon and energy-limiting conditions [67]. More recently, it was demonstrated that apoplastic EXO protein modifies intracellular sucrose and trehalose responses and thus connects the extracellular C status to growth [68]; trehalose feeding induced Arabidopsis EXO expression, and therefore a potential increase in trehalose synthesis after AcTPS1 .…”
Section: Discussionmentioning
confidence: 99%
“…EXORDIUM (EXO) is another relevant gene found in this work, previously described in proliferating cells (Farrar et al 2003). First, it was suggested to be a negative regulator of cell division control and meristem maintenance.…”
Section: Degs Involved In Lw Developmentmentioning
confidence: 76%